Complementarity of Management Control Mechanisms in a Lean Organization: The Effect of Consensus - Kevin Hermanto Tupamahu (Journal of Economics, Business, and Accountancy Ventura, 2022)
This study aims to examine the complementarity effect of lean management control mechanisms (lean performance measurement, employee empowerment, visual control, standard operating procedures, and peer pressures) on company performance (operations and financial performance). Besides, this study also tests whether the consensus on lean thinking has affected the relationship between the lean management control mechanisms and the company’s performance. The data is collected by survey with 159 managers from manufacturing companies. The data is then analyzed using the AMOS-SEM and shows that lean management control mechanisms work complementary to increase operation and financial performance in lean manufacturing companies. Furthermore, consensus on lean thinking strategies acts as a moderating variable and positively affects the relationship between lean management control mechanisms and financial performance. This study recommends that lean companies should implement control mechanisms that align with lean thinking. These control mechanisms should be used together to complement each other to maximize the performance benefits that can be derived from lean thinking implementation. In addition, to strengthen the benefits derived from the use of lean control mechanisms, companies need to pay attention to the consensus in implementing lean thinking strategies.